The Service Quality and Marketing Mix Influence to Customer Satisfaction of Pertamina Petrol Station - Johan Johan (Applied Quantitative Analysis, 2023)
A petrol station company is usually classified as a trading company that sells fuel to customers. The service quality variable is as important as the goods (fuel) trading. The research area was in the Pertamina petrol station in Riau province. This study aims to examine the significant influence of service quality and marketing mix variables on customer satisfaction at Pertamina Petrol Stations, and to identify differences in customer satisfaction across gender perspectives in Riau province. The sample for this study consisted of petrol station customers in Riau province, with 200 respondents selected using probability sampling methods. The data were processed using Smart PLS structural equation modelling (SEM) statistics. The findings revealed a positive relationship between service quality and customer satisfaction. The marketing mix positively influenced customer satisfaction. The significance level of the difference in customer satisfaction by gender was determined using probability sampling with 200 respondents. The data were processed using Smart PLS for structural equation modelling (SEM). The findings revealed a positive relationship between service quality and customer satisfaction. The marketing mix had a positive influence on customer satisfaction. The significance level of the difference in customer satisfaction by gender was determined using probability sampling with 200 respondents. The data were processed using Smart PLS for structural equation modelling (SEM). The findings revealed a positive relationship between service quality and customer satisfaction. The marketing mix had a positive influence on customer satisfaction.